The Integration of Design Thinking in MSME Digital Transformation in the Platform Economy Era: A Bibliometric Analysis and Systematic Literature Review - Marthina Ari; Muafiqa Natsir; Suardam Djamadi; Mozes Haryanto; Megawaty Megawaty (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to examine the development of research on the integration of design thinking in the digital transformation process of Micro, Small, and Medium Enterprises (MSMEs) in the platform economy era, while also developing a more integrated conceptual model. This study employs a Systematic Literature Review (SLR) method combined with bibliometric analysis using VOSviewer. The findings show that studies on design thinking, digital transformation, and the platform economy are still developing separately and have not been widely integrated into a comprehensive conceptual framework. The bibliometric visualization indicates the dominance of keywords such as “Indonesia,” “digital transformation,” and “design thinking,” as well as the emergence of new themes such as QRIS and artificial intelligence in recent publications. Based on these findings, this study proposes a conceptual model entitled “Design Thinking–Driven MSME Transformation,” which connects the understanding of user needs, digital strategy, and the utilization of platform ecosystems. This model is expected to enrich theoretical development while also serving as a practical reference for MSMEs in addressing the challenges of digital transformation.